2016
DOI: 10.3168/jds.2015-9745
|View full text |Cite
|
Sign up to set email alerts
|

Two approaches to improve fertility of subclinical mastitic dairy cows

Abstract: Mastitis, particularly in its subclinical form, is a widely spread disease that reduces the fertility of lactating cows. A major cause of poor conception risk has been associated with delayed ovulation of a large subgroup of subclinical mastitic cows. This study examined 2 approaches to improve fertility in this subgroup. Subclinical mastitic cows were defined by somatic cell count elevated above a threshold of 150,000 cells/mL of milk determined in all monthly test day samples collected before AI. Uninfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The major finding was that "Ovsynch" increased conception in subclinical mastitic cows to rates similar to those in controls, whereas the conception rate of mastitic cows that were artificially inseminated after natural estrus remained low. Conception rates for uninfected-AI at estrus, subclinical-AI at estrus, uninfected-AI after "Ovsynch" and subclinical-AI after "Ovsynch" groups were 41.8%, 26.4%, 39.3%, and 40.5%, respectively [102]. Results suggested that the "Ovsynch" protocol can improve fertility of subclinical mastitic cows, most likely via synchronization of ovulation timing in cows in which it would otherwise be delayed.…”
Section: Strategies To Improve Fertility Of Mastitic Cowsmentioning
confidence: 90%
See 2 more Smart Citations
“…The major finding was that "Ovsynch" increased conception in subclinical mastitic cows to rates similar to those in controls, whereas the conception rate of mastitic cows that were artificially inseminated after natural estrus remained low. Conception rates for uninfected-AI at estrus, subclinical-AI at estrus, uninfected-AI after "Ovsynch" and subclinical-AI after "Ovsynch" groups were 41.8%, 26.4%, 39.3%, and 40.5%, respectively [102]. Results suggested that the "Ovsynch" protocol can improve fertility of subclinical mastitic cows, most likely via synchronization of ovulation timing in cows in which it would otherwise be delayed.…”
Section: Strategies To Improve Fertility Of Mastitic Cowsmentioning
confidence: 90%
“…Recently, a study aiming at improving fertility of subclinical mastitic cows was performed [101,102]. The assumption was that "correcting" the timing of ovulation in subclinical mastitic cows exhibiting delayed ovulation could improve their conception rate.…”
Section: Strategies To Improve Fertility Of Mastitic Cowsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was followed by a study that identified similar detrimental effects for cows affected with subclinical mastitis during the early breeding period (Schrick et al, 2001). Since that time, numerous researchers have confirmed that even relatively modest levels of inflammation can affect fertility, and the effect of inflammation caused by mastitis beyond the mammary gland continues to be an important area of research (Lavon et al, 2011(Lavon et al, , 2016Hudson et al, 2012;Fuenzalida et al, 2015).…”
Section: Impact Of Mastitismentioning
confidence: 94%
“…McDougall and Voermans (2002) attributed the decrease in milk yield during estrus to an increased SCC level in goats when using two different estrus synchronization methods. Lavon et al (2016) reported pregnancy rates in cattle treated with the Ovsynch protocol that were similar to cattle without mastitis. Based on this finding, the Ovsynch protocol was proposed as a means of increasing fertility in cattle with subclinical mastitis.…”
Section: Discussionmentioning
confidence: 93%